2019
DOI: 10.1177/1078155218821406
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a urine alkalinization protocol developed for high-dose methotrexate patients during intravenous bicarbonate shortage

Abstract: Purpose Urinary alkalinization with intravenous sodium bicarbonate is standard during high-dose methotrexate administration. Due to a national intravenous sodium bicarbonate shortage, a urinary alkalinization protocol involving hyperhydration with intravenous fluids, oral bicarbonate, and intravenous or oral acetazolamide was utilized from 10 April to 30 May 2017 (“shortage protocol”). This study compared outcomes between protocols. Methods A single-center, retrospective chart review was conducted for adults w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 10 publications
3
17
0
Order By: Relevance
“…This study did not show a difference in toxicities or time to clearance of MTX; however, adverse effects of the protocol were not reported. 15 Neither of these previous studies included combination therapy for urine alkalinization.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not show a difference in toxicities or time to clearance of MTX; however, adverse effects of the protocol were not reported. 15 Neither of these previous studies included combination therapy for urine alkalinization.…”
Section: Discussionmentioning
confidence: 99%
“…Roy et al. 16 reported that adherence to oral NaHCO 3 was only 67.5% due to pill burden in an adult population, and NaHCO 3 suspension was utilized over tablets in some patients. Similarly, Visage et al.…”
Section: Discussionmentioning
confidence: 99%
“…PO alkalization regimens in literature were limited at the time of the national shortage. Roy et al recently published another institution’s protocol for PO alkalization in the time of the national shortage 15. Their HDMTX “shortage” protocol included PO sodium bicarbonate at 3250 mg every 2 hrs in addition to PO or IV acetazolamide 250–500 mg every 6 hrs as needed.…”
Section: Discussionmentioning
confidence: 99%
“…When used alone, prolonged carbonic anhydrase inhibition with acetazolamide results in depletion of the bicarbonate-carbon dioxide buffer in blood and could eventually lead to loss of urine alkalization followed by worsening MTX crystallization in the kidney tubules. Roy et al investigated an PO alkalization regimen similar to ours with sodium bicarbonate and PO acetazolamide; however, they used higher doses and more frequent PO sodium bicarbonate and reserved acetazolamide for use as needed when urine pH was <7.5 15Table 6Overview of previously published alternative regimens to intravenous sodium bicarbonate for urine alkalizationAuthorRegimenComparator armOutcomesAdverse eventsShamash et al8Acetazolamide 500 mg IV every 6 hrs for 48 hNo comparatorNo delayed clearanceNo significant AEsRouch et al7Sodium bicarbonate: 650 mg tablet orsodium citrate 500 mg/ citric acid 334 mg/ 5 mL every 6 hrsParenteral sodium bicarbonate (50–150 mEq) physician preferenceNo difference in AKI or hepatic injuryDiarrhea P =0.002Visage et al17Sodium bicarbonate: 1950 mg/m 2 or Sodium citrate-citric acid oral solution: 22.5 mEq/m 2 /dose every 6 hrsNo comparatorDelayed clearance seen in 2% of casesGI side effects reported in 43%Roy et al15Sodium bicarbonate: 3250 mg PO every 12 hrsAcetazolamide 250 mg-500 mg PO or IV every 6 hrs PRN urine pH <7.5+ possible outpatient alkalinizationIntravenous sodium bicarbonate (150 mEq per 1000 mL) AND oral sodium bicarbonate at 3250 PO every 4 hrs PRN for urine pH <7.5No difference in MTX clearanceIncrease in LOS P =0.23No difference in toxicity (AKI, hepatoxicity, myelosuppression)No difference in change in creatinine clearanceAlrabiah et al18Sodium acetate IVParenteral sodium bicarbonateNo difference in LOS, time to pH >8, MTX clearance, or AKINo adverse events identified Abbreviations: MTX, methotrexate; PO, oral; IV, intravenous; LOS, length of stay; PRN, as needed; GI, gastrointestinal. …”
Section: Discussionmentioning
confidence: 99%